Implications of Macro Economic Conditions for Banking Effectiveness in Indonesia - Ningsih, Nuri Rahayu; Rusdianto, Budi; Siregar, Kardina; Zulfa, Andria; Sakuntala, Dwita (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
This research aims to determine banking effectiveness. The variables in this research are Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Economic Growth (GDP), Inflation, and Exchange Rates. The analytical method used in this research is the Vector Auto Regression (VAR) model with the Impulse Response Function (IRF) test, Forecast Error Variance Decomposition (FEVD), stationarity test, cointegration test, structural lag stability test, and optimal lag length test. The results of Vector Autoregressive research using a lag 2 basis show that there is a contribution from each variable to the variable itself and other variables. The results of the Vector Autoregression analysis also show that the past variable (t-1) contributes to the current variable, both the variable itself and other variables. From the analysis results, there is a reciprocal relationship between one variable and another variable. Response Function analysis shows that there is a response of other variables to changes in one variable in the short, medium, and long term, and it is known that the stability of the response of all variables is formed in 5 years or long term. Variance Analysis Decomposition shows the existence of variables that have the largest contribution to the variable itself in the short, medium, and long term, such as INF and KURS. Meanwhile, other variables that have the greatest influence on the variable itself and are supported by other variables in the short, medium, and long term are CAR and NPL which are most influenced by the EXCHANGE and GDP.